2006
DOI: 10.1038/ng1894
|View full text |Cite
|
Sign up to set email alerts
|

Irf6 is a key determinant of the keratinocyte proliferation-differentiation switch

Abstract: The epidermis is a highly organized structure, the integrity of which is central to the protection of an organism. Development and subsequent maintenance of this tissue depends critically on the intricate balance between proliferation and differentiation of a resident stem cell population; however, the signals controlling the proliferation-differentiation switch in vivo remain elusive. Here, we show that mice carrying a homozygous missense mutation in interferon regulatory factor 6 (Irf6), the homolog of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
367
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 293 publications
(403 citation statements)
references
References 27 publications
23
367
0
Order By: Relevance
“…An abnormal skin architecture resembling that of RIPK4 − / − mice was also reported for IRF6 − / − mice, which have a defective skin barrier. 10,11 In WT mice, the skin barrier starts forming at E16 and is fully functional at E17. 18 Dye exclusion assays showed that toluidine blue and lucifer yellow penetrate E18.5 RIPK4 − / − skin but not RIPK4 +/+ skin (Figures 2a and b), indicating that a mature outside-in barrier is not formed in RIPK4 − / − skin.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…An abnormal skin architecture resembling that of RIPK4 − / − mice was also reported for IRF6 − / − mice, which have a defective skin barrier. 10,11 In WT mice, the skin barrier starts forming at E16 and is fully functional at E17. 18 Dye exclusion assays showed that toluidine blue and lucifer yellow penetrate E18.5 RIPK4 − / − skin but not RIPK4 +/+ skin (Figures 2a and b), indicating that a mature outside-in barrier is not formed in RIPK4 − / − skin.…”
Section: Resultsmentioning
confidence: 99%
“…The RIPK4 − / − mouse phenotype we observed is similar to that of the IRF6 − / − and the IRF6 R84C/R84C mice. 10,11 Moreover, similar to RIPK4 activity, IRF6 is also required for gastrulation in Danio rerio and X. laevis. 28 Until now, there is no evidence that functionally connects these two molecules.…”
Section: G H and I)mentioning
confidence: 98%
See 3 more Smart Citations